2021
DOI: 10.1021/acs.jpcc.0c09929
|View full text |Cite
|
Sign up to set email alerts
|

High Thermoelectric Performance in the Cubic Inorganic Cesium Iodide Perovskites CsBI3 (B = Pb, Sn, and Ge) from First-Principles

Abstract: Searching thermoelectric materials with high performance and low cost is now receiving special attention and great challenges in the field of material design. In this work, we perform first-principles lattice dynamics combined with temperature-induced anharmonic phonon renormalization and connected to the Boltzmann transport equation to predict thermoelectric performance in the cubic inorganic iodide perovskites CsBI3 (B = Pb, Sn, and Ge) at a high temperature of 700 K. Under stabilization of the cubic phase t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…In the design of promising candidates for high performance TEMs, the primary interest was focused on innovative materials with intrinsically ultralow thermal conductivity. 19 Such ultralow thermal conductivity has been found in complex materials with complicated compositions 7,20,21 or disordered layered structures 22–26 and in simple crystalline materials such as halide perovskites 27–33 and dichalcogenides. 34–37 In these materials, the heat carriers are mostly phonons, being highly anharmonic, and strong phonon–phonon 27,38 or phonon-disorder scattering 39 is the main mechanism for lowering the thermal conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…In the design of promising candidates for high performance TEMs, the primary interest was focused on innovative materials with intrinsically ultralow thermal conductivity. 19 Such ultralow thermal conductivity has been found in complex materials with complicated compositions 7,20,21 or disordered layered structures 22–26 and in simple crystalline materials such as halide perovskites 27–33 and dichalcogenides. 34–37 In these materials, the heat carriers are mostly phonons, being highly anharmonic, and strong phonon–phonon 27,38 or phonon-disorder scattering 39 is the main mechanism for lowering the thermal conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the ZT values of SnSe, Bi 2 O 2 Se, and LaCuOSe are reported to be about 2.6 at 923 K, 5.9 at 800 K, and 2.71 at 900 K, 26,28,61 respectively. Furthermore, the ZT value of CaZrS 3 is much higher than that of typical inorganic halide perovskites such as CsPbI 3 , CsSnI 3 , and CsGeI 3 , for which the maximum ZT values are reported to be 0.45, 0.95, and 1.05 at a stable temperature of 700 K, 62 respectively. Therefore, it suggested that the excellent TE performance of orthorhombic CaZrS 3 can be realized by adjusting the carrier concentration, indicating the potential to become an excellent TE material for CaZrS 3 .…”
Section: Figure Of Meritmentioning
confidence: 91%
“…2 shows the maximum ZT achieved for bulk thermoelectric materials over the past six years as a function of temperature. 33–234…”
Section: Strategiesmentioning
confidence: 99%